2017
DOI: 10.1371/journal.pone.0172756
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal and non-invasive prenatal detection of β-thalassemia mutations based on Taqman genotyping assays

Abstract: The β-thalassemias are genetic disorder caused by more than 200 mutations in the β-globin gene, resulting in a total (β0) or partial (β+) deficit of the globin chain synthesis. The most frequent Mediterranean mutations for β-thalassemia are: β039, β+IVSI-110, β+IVSI-6 and β0IVSI-1. Several molecular techniques for the detection of point mutations have been developed based on the amplification of the DNA target by polymerase chain reaction (PCR), but they could be labor-intensive and technically demanding. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…When notified about the results of the mother’s blood test, most of the mothers chose to not undergo additional checks, such as invasive prenatal diagnosis. 10-12 Currently, there are many techniques for detecting paternally inherited beta thalassemia mutations, including nextgeneration sequencing, 13 COLD-PCR and microarrays, 14 next-generation sequencing of SNPs, 15 TaqMan genotyping assay, 16 droplet digital PCR 17 and simple fetal DNA enrichment with allele-specific real-time PCRs. 18-22 The ARMS RT- PCR technique was simple, accurate, cost-effective, and able to detect paternally inherited beta thalassemia mutations directly from cell-free DNA in maternal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…When notified about the results of the mother’s blood test, most of the mothers chose to not undergo additional checks, such as invasive prenatal diagnosis. 10-12 Currently, there are many techniques for detecting paternally inherited beta thalassemia mutations, including nextgeneration sequencing, 13 COLD-PCR and microarrays, 14 next-generation sequencing of SNPs, 15 TaqMan genotyping assay, 16 droplet digital PCR 17 and simple fetal DNA enrichment with allele-specific real-time PCRs. 18-22 The ARMS RT- PCR technique was simple, accurate, cost-effective, and able to detect paternally inherited beta thalassemia mutations directly from cell-free DNA in maternal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Sanjay Piplani et al have studied the utility of NESTROFT in 150 Indian Punjabi subjects and have concluded that it is a cost-effective, valuable screening test in the rural population 3 . Giulia Breveglieri et al have studied the Taqman genotyping for detection of single nucleotide polymorphisms frequent in thalassemias 4 . They have observed in their study that these genotyping methods could be used for non-invasive prenatal diagnosis of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, in beta thalssemia trait, due to alteration in osmotic resistance of the affected RBC"s due to volume/surface area ratio changes [4] lysis begins at a saline concentration between 0.4-0.35% and it may not be completed even at 0.1% solution. NESTROFT is done at a saline concentration of 0.36% to ensure a high sensitivity with acceptable specificity.…”
Section: Principle Of Nestroftmentioning
confidence: 99%
“…Comprehensive screening programs highlighted recognizing carriers and offering prenatal diagnosis in pregnancies for thalassemia have been incorporated in Canada and European countries [72,73]. Different procedures have been implimented to distinguish thalassemia like genotyping assay, genotyping measur next-generation sequencing and mass spectrometry [74][75][76]. The methods are as yet testing; consequently, more investigations are expected to create and approve them and eventually lead to proficient, exact and concrete non-invasive prenatal diagnosis of thalassemia and hemoglobinopathies [77].…”
Section: Prenatal Screeningmentioning
confidence: 99%